THE EFFECTIVENESS OF QUANTUM LEARNING MODEL TOWARD EIGHT GRADE STUDENTS’ READING SKILLS IN SMP N 12 BINTAN - Raudah Raudah (STAIN Sultan Abdurrahman Kepulauan Riau, 2020)
This study aims at analyzing the implementation of Quantum learning model for EFL learners at SMP N 12 Bintan, Kepulauan Riau province. Urged by the factual situation that lack of students’ reading ability, the chosen model was applied in the form of classroom action research. The subject of the study is 31 of eight grade students. The result showed the application of the Quantum learning model improves students' ability to read text. This is indicated by an increase in reading skills from pre-cycle which only averaged 75.23 to 78.52 in the first cycle, while the percentage of completeness increased from 35% to 84%. In cycle II, with the improvement of Quantum learning accompanied by encouragement from teachers and guidance in groups to actively ask questions, feedback, reinforce, and divide heterogeneous groups, the average score increased to 82.29, and the percentage of completeness increased to 100%.